2012
DOI: 10.1007/s12020-012-9627-x
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of insulin resistance in patients with normocalcemic primary hyperparathyroidism

Abstract: While derangements in glucose metabolism in patients with primary hyperparathyroidism are well-defined, this issue is not investigated in patients with normocalcemic primary hyperparathyroidism (NPHPT). The aim of this study was to investigate the presence of insulin resistance in patients with NPHPT. Eighteen patients with NPHPT (two males and 16 females) and 18 healthy volunteers were enrolled into the study. Secondary causes of parathyroid hormone elevations were excluded in all patients. Blood samples were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 19 publications
0
25
0
Order By: Relevance
“…Noteworthy our data show a positive correlation between serum total calcium levels and insulin resistance. Consistently, recent studies do not find an increased insulin resistance in patients with normocalcemic PHPT [34,35]. However, it has to be underlined that cytosol calcium content seems more important than serum calcium to influence insulin secretion and sensitivity [36].…”
Section: Discussionmentioning
confidence: 80%
“…Noteworthy our data show a positive correlation between serum total calcium levels and insulin resistance. Consistently, recent studies do not find an increased insulin resistance in patients with normocalcemic PHPT [34,35]. However, it has to be underlined that cytosol calcium content seems more important than serum calcium to influence insulin secretion and sensitivity [36].…”
Section: Discussionmentioning
confidence: 80%
“…But limited data are available in NC-PHPT for insulin sensitivity. A case-control study reported by Cakir et al investigated insulin resistance in NC-PHPT patients [16]. In this study, 18 patients with NC-PHPT and 18 matched controls had comparisons of glucose metabolism as assessed by OGTT.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether NC-PHPT carries the same risk for increased CV morbidity as the hypercalcemic form [13]. There are few and contradictory data available regarding metabolic abnormalities of normocalcemic PHPT patients in the literature [12,[14][15][16].…”
mentioning
confidence: 99%
“…Tordjman and cols., evaluated a cohort comprising 32 patients with normocalcemic hyperparathyroidism and found a high prevalence of osteoporosis (36%), with 9% presenting nephrolithiasis (7). Cakir and cols., in their investigation of 18 patients with normocalcemic hyperparathyroidism and a mean age of 50 years (47% female) found that 47% had osteoporosis and 11% nephrolithiasis (8).…”
Section: Case Reportmentioning
confidence: 98%